Lexical Choice and Rhetorical Expression - Peter Feldmeier (International Institute of Islamic Thought, 2018)
Many religions understand themselves as fundamentally aligned to a given culture or people. Hinduism is intrinsically connected to the Indian culture and caste system. Daoism and Confucianism are highly integrated into the Chinese spirit and the cultural mentality of the Orient. Shinto’s cosmology, myths, and rites concern themselves solely with the Japanese. Even in the West, Judaism locates itself with the people of Israel. Jews welcome converts, but Judaism has never seen itself as a proselytizing religion. Islam is convinced that Muhammad’s message is both universal and constitutes the highest revelation. Thus, it is a proselytizing religion. But Muslims historically and today believe that non-Muslims can be saved in the context of their own religious traditions, particularly if these are monotheistic. Christianity perhaps stands alone as a religion that has historically believed that membership in the church is necessary for salvation. Add to this that Roman Catholicism had believed that Catholic membership was necessary. As the Fourth Lateran Council (1215) declared, “There is only one universal church of the faithful, outside which none can be saved.” More recently, most Christians, including Catholics, think that God’s saving grace is available outside its ecclesial boarders, but this is a modern idea. What then to think of the religious other? In the seventeenth century, a Catholic had few conceptual choices. One was to consider religious others and their sacred texts as valuable preparation for the gospel, and thus admire what could be admired in them. They had something of what St. Justin Martyr called the Logos spermatikos, seeds of the Word. This included the principle of inculturation whereby European culture was not to be conflated with Christianity. This principle became policy, at least in theory, ...